The Influence of Emotional Intelligence and Transformational Leadership on Employee Performance Mediated by Employee Satisfaction at Bulukumba Regent's Office - Awaliya, Nurdia; Mappatompo, Andi; AC, Ahmad (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
The purpose of this study is to ascertain how employee satisfaction at the Bulukumba Regent's Office mediates the impact of transformational and emotionally intelligent leadership on worker performance. A survey of 104 respondents was used to collect data for this quantitative investigation. The majority of respondents (41.35%) were between the ages of 31 and 40, followed by those between the ages of 41 and 50 (29.81%), had a bachelor's degree (65.38%), had worked for 5 to 10 years (34.62%), followed by those between the ages of 11 and 15 (22.1%), and held staff jobs (68.27%), according to the data. According to the study's findings, employee satisfaction is not impacted by emotional intelligence, emotional intelligence affects employee performance, employee satisfaction affects employee performance, transformational leadership affects employee satisfaction, transformational leadership does not affect employee performance, and employee satisfaction does not mediate transformational leadership on employee performance.